The gender gap in financial literacy: Income, education, and experience offer only partial explanations - Antonia Grohmann (DIW Economic Bulletin, 2016)
In most countries, women have a lower level of financial literacy than men on average. This report demonstrates that differences in income and education and less experience in financial matters only provide a partial explanation for the gender gap. Data from various countries show that cultural differences may also play a role. In order to close the gender gap in financial literacy, schools should do a better job of imparting general knowledge and numerical proficiency. Lessons on the subject of finance must attempt to involve girls so they learn to view financial matters as part of 'their job' from an early age. Overall gender equality would also narrow the gender gap in financial literacy.
Keywords: D14; J16; D91; 330; Financial literacy; Financial Behavior; Gender Gaps; Individual Characteristics; Societal Norms